2011
DOI: 10.1073/pnas.1007640108
|View full text |Cite
|
Sign up to set email alerts
|

Reversible modulations of neuronal plasticity by VEGF

Abstract: Neurons, astrocytes, and blood vessels are organized in functional “neurovascular units” in which the vasculature can impact neuronal activity and, in turn, dynamically adjust to its change. Here we explored different mechanisms by which VEGF, a pleiotropic factor known to possess multiple activities vis-à-vis blood vessels and neurons, may affect adult neurogenesis and cognition. Conditional transgenic systems were used to reversibly overexpress VEGF or block endogenous VEGF in the hippocampus of adult mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
197
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(211 citation statements)
references
References 33 publications
12
197
2
Order By: Relevance
“…In line with such a role of VEGF, it was recently reported that conditional transient increase of VEGF expression for 5-15 days leads to significant increase of long-term potentiation in the hippocampus through modulation of synaptic plasticity in mature neurons [41]. In addition, VEGF has been implicated as a mediator of human NSC-induced effects on dendritic sprouting, axonal plasticity, and axonal transport [15].…”
Section: Discussionmentioning
confidence: 88%
“…In line with such a role of VEGF, it was recently reported that conditional transient increase of VEGF expression for 5-15 days leads to significant increase of long-term potentiation in the hippocampus through modulation of synaptic plasticity in mature neurons [41]. In addition, VEGF has been implicated as a mediator of human NSC-induced effects on dendritic sprouting, axonal plasticity, and axonal transport [15].…”
Section: Discussionmentioning
confidence: 88%
“…In addition, blood circulating factors have substantial effects over the process of neurogenesis (79)(80)(81)(82). VEGF is one of these factors (83), and can stimulate neurogenesis (84)(85)(86) and reversibly modulate neuronal plasticity (87). Other blood-derived factors capable of affecting neurogenesis are glucocorticoids, which are necessary for the regulation of neuronal differentiation and migration (88).…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-A (VEGF) is a pro-angiogenic factor [20,21] that is also involved in neuroprotection, neurogenesis, synaptic plasticity, and modulation of inflammation and astrocyte proliferation [22][23][24][25][26]. It is upregulated in response to hypoxia [27,28] and elevated within hypoperfused cortex and white matter in small vessel disease, vascular dementia and AD [3,[29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%